2009
DOI: 10.1001/archgenpsychiatry.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Internet-Based Behavioral Intervention for Adults With Insomnia

Abstract: Context: Insomnia is a major health problem with significant psychological, health, and economic consequences. However, availability to one of the most effective insomnia treatments, Cognitive Behavioral Therapy (CBT), is significantly limited. The Internet may be a key conduit for delivering this intervention. Objective: To evaluate the efficacy of a structured behavioral Internet intervention for adults with insomnia. Design, Setting, and Participants: 45 adults were randomly assigned to an Internet inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
305
2
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(334 citation statements)
references
References 44 publications
17
305
2
10
Order By: Relevance
“…Our effect size compared to control was moderate, and tallies with studies finding that iCBT can be effective for reducing insomnia in both community (Ritterband, et al, 2009;Ström et al, 2004) and patient (Vincent & Lewycky, 2009) populations, with effect sizes ranging from small to moderate (Ström et al, 2004) and small to large (Vincent and Lewycky, 2009). …”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our effect size compared to control was moderate, and tallies with studies finding that iCBT can be effective for reducing insomnia in both community (Ritterband, et al, 2009;Ström et al, 2004) and patient (Vincent & Lewycky, 2009) populations, with effect sizes ranging from small to moderate (Ström et al, 2004) and small to large (Vincent and Lewycky, 2009). …”
Section: Discussionsupporting
confidence: 75%
“…Ritterband, et al (2009) found that an internet delivered program was effective at reducing insomnia in a US community sample of insomnia sufferers. Ström, Pettersson & Andersson (2004) found that an iCBT A c c e p t e d M a n u s c r i p t 6 ICBT FOR ANXIETY AND INSOMNIA IN UNDERGRADUATES program for insomnia was effective at improving sleep time, total wake time in bed, and sleep efficiency in a Swedish community sample of insomnia sufferers, albeit with small effect sizes.…”
Section: Internet-delivered-cognitive Behavioural Therapy (Icbt) For mentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, using established treatment outcome criteria, 69.7% were considered treatment responders and 56.6% were considered in remission at the final assessment point (1-year post treatment) in the SHUTi condition compared to 43% and 27.3%, respectively, in the control condition. Interestingly the effect sizes reported broadly match those typically seen in CBT-I studies employing face-to-face methods (15). Of note, however, almost 40% (39.7%) of those enrolled to the SHUTi condition did not complete all the prescribed modules.…”
supporting
confidence: 69%